ERP Enhancement to Accommodate Business Process in Furnishing Company - Firmansyah, Deny (Journal of Applied Information, Communication and Technology, 2015)
Avoiding customization to enhance of an ERP implementation consider as one of successful keyfactor. Within this paper, the writer tries to answer the question of â€œThe expectation of ERP able tofit in with company business flow in a standard way and why enhancing the system is almost notavoidableâ€.To answer this question, the writer will use a case study of a furnishing distribution company or thesupplier to retail store in the process of integration of ERP system with logistic process.